Clinical perspectives and concerns of metformin as an anti‐aging drug. Issue 4 (1st December 2020) - Wang, Chuyao; Chen, Bangwei; Feng, Qian; Nie, Chao; Li, Tao
Abstract: As percentages of elderly people rise in many societies, age‐related diseases have become more prevalent than ever. Research interests have been shifting to delaying age‐related diseases by delaying or reversing aging itself. We use metformin as an entry point to talk about the important molecular and genetic longevity‐regulating mechanisms that have been extensively studied with it. Then we review a number of observational studies, animal studies, and clinical trials to reflect the clinical potentials of the mechanisms in lifespan extension, cardiovascular diseases, tumors, and neurodegeneration. Finally, we highlight remaining concerns that are related to metformin and future anti‐aging research. Abstract : In this paper, we review mechanisms and clinical studies of metformin. Papers reviewed include studies in longevity, cardiovascular diseases, cancer, and neurodegeneration. In the end, we provide insights to guide future research.